Hardened state behaviour of self-compacting concrete pavement mixes containing alternative aggregates and secondary binders. (10th January 2021) - Singh, Ran Bir; Debbarma, Solomon; Kumar, Navanit; Singh, Surender
Highlights: Effect of RCAs on hardened state behaviour of two grades of SCC pavement mixes was investigated. Suitability of designed concrete mixes were evaluated for their effective utilization in SCC-CRCP. Application of 100% RCAs is suggested in high volume fly ash self-compacting concrete pavement mixes. Abstract: Hardened state behaviour of two grades (normal- and medium-strength) of Self-Compacting Concrete (SCC) pavement mixes containing varying proportions of Recycled Concrete Aggregates (RCAs) as an alternative aggregate is reported in this paper. These two SCC grades were designed by varying the proportions of fly ash, silica fume and metakaolin in binary and ternary blends of Portland cement. The suitability of these mixes were evaluated for Continuously Reinforced Concrete Pavements (CRCP) application considering various performance as well as the quality control parameters. The results (both experimental and analytical) depicted that inclusion of RCA in Saturated-Surface-Dry (SSD) moisture state would not have any negative effect on fresh and hardened state behaviour of the SCC-CRCP mixes. Although the cement content in some of the mixes were higher than the recommended limit, all the mixes could meet the minimum stipulated flexural strength criterion of 4.5 MPa at 28 days of curing for CRCP. However, to maximize the benefit (utilizing fewer natural resources and more recycled materials) without compromising with the engineering properties, high-volume fly ash based (50%) normal-grade SCC containing 100% RCAs is recommended.